Model based examination of radiocarbon contribution from Indonesian throughflow to the south-eastern tropical Indian Ocean. (June 2023) - Raj, Harsh; Narang, Ashish; Bhushan, Ravi
Abstract: Shallow seawater coral records from the south-eastern tropical Indian Ocean region can be investigated to study Indonesian throughflow (ITF). In this study, the radiocarbon records of Porites corals were used to estimate lateral transport via ITF and to understand the influence of ITF on radiocarbon levels of surface waters in the south-eastern tropical Indian Ocean. A simple box model based on radiocarbon was applied for this purpose. Model estimated a mean lateral transport via ITF to be 12.5 × 10 6  m 3  s −1 towards the south-eastern tropical Indian Ocean region using pre-bomb radiocarbon records. The model was further used to reconstruct post-bomb radiocarbon level in the Cocos Island surface water and result was compared with the observed value. The box model result demonstrated that along with air-sea CO2 exchange, the ITF was also an important contributor of bomb radiocarbon to the surface water of the south-eastern tropical Indian Ocean. The box model showed that the ITF significantly contributed bomb radiocarbon to the surface water of the south-eastern tropical Indian Ocean after the rapid increase in bomb radiocarbon in the region. Highlights: Box model based on 14 C was applied to study the Indonesian throughflow (ITF). 12.5 × 10 6  m 3  s −1 mean transport via ITF was estimated from pre-bomb 14 C records. ITF significantly contributed bomb 14 C to the Cocos Island region after mid 1970s.